Multiliteracy in English Department Universitas Muhammadiyah Sidoarjo - Ermawati Z Nuroh; Tri Linggo Wati; Ida Rindaningsih (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
This research aims to describe multiliteracy model in the lecture Introduction to Literature, semester 3 students of English Department, Universitas Muhammadiyah Sidoarjo. Research methods that will be used is qualitative descriptive on the lecture Introduction to Literature. Research data obtained from the results of questionnaires and interviews with students, student assignment documents, learning materials and assessment system of the lecturer. The data in this study were collected through observation which is equipped with observation, interviews with guidelines based on the guidelines of the interview, the document to see the response of the students, as well as documented through photos and videos. All data are then analyzed and checked each other. The validity and reliability of research accomplished through member check and outsider check. Discussion and consultation with experts and literature, language learning and literacy experts conducted to obtain accurate data. The research was conducted in two stages, among other things: 1)Â research on the multiliteracy aspects of student in the English Department, which is reflected in multiliteracy competence in Introduction to Literature lecture; 2) research on the studentsâ€™ responseÂ against the multiliteracy competence in the lecture of Introduction to literature.